(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
The shell of Thecospira tyrolensis (Loretz) is characterized by three distinct layers consisting of low Mg-calcite. The primary layer consists of microcrystalline calcite and it is often diagenetically altered. The secondary layer is composed of imbricate fibres subparallel to the valve surface. The tertiary layer (prismatic) is made of calcite prisms perpendicular to the outer epithelium of the mantle and was formed by ephitelial cells that reverted to inorganic secretion. For this reason, as well as its morphology, the prismatic layer can be compared to some pore-filling low Mg-calcites, therefore we would expect it to follow inorganic nucleation and growth theory. Transmission electron microscopy allowed to recognize crystal defects (sets of microtwins and dislocations) which, by creating abutting surfaces and kinks, represent favourable sites where new "calcite seeds" attach themselves to the crystal surface. Stacking of (hkil) planes where growth is faster (in particular the basal piane), favoured by twinning, accounts for the prismatic habit.